Workplace improvements to support safe and sustained return to work: Suggestions from a survey of workers with permanent impairments. Issue 9 (12th July 2021) - Sears, Jeanne M.; Edmonds, Amy T.; MacEachen, Ellen; Fulton‐Kehoe, Deborah
Abstract: Background: Roughly 10% of occupational injuries result in permanent impairment. After initial return to work (RTW), many workers with permanent impairments face RTW interruption due to reinjury, unstable health, disability, and layoff. This study used open‐ended survey data to: (1) explore workplace factors identified by workers as important levers for change, some of which may previously have been unrecognized; and (2) summarize workers' suggestions for workplace improvements to promote sustained RTW and prevent reinjury. Methods: This study included data from workers' compensation claims and telephone surveys of 582 Washington State workers who had RTW after a work‐related injury involving permanent impairment. The survey was conducted in 2019, about a year after claim closure. We used qualitative content analysis methods to inductively code open‐ended survey responses. Results: The most frequent themes were: safety precautions/safer workplace (18.1%), adequate staffing/appropriate task distribution (16.2%), and safety climate (14.1%). Other frequent themes included ergonomics, rest breaks, job strain, predictability and flexibility in work scheduling practices, employer response to injury, social support, communication, and respect. Many workers reported that they were not listened to, or that their input was not sought or valued. Workers often linked communication deficiencies to preventable deficiencies in safety practices, safety climate, and RTW practices, and also to lack of respect or distrust. In counterpoint, nearly one‐third of respondents reported that no change was needed to their workplace. Conclusions: Policies and interventions targeting worker‐suggested workplace improvements may promote safe and sustained RTW, which is essential for worker health and economic stability.